From Academician to Politician Asafri Jaya Bakri’s (AJB) Career Journey 1984-2021 - Aditama, Irwan; Asnan, Phil Gusti; Nopriyasman, Nopriyasman (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
In the reform era, there are several unique symptoms/phenomena, one of which is the development of human resources (HR), namely the transition of professions.This research aims to look at the career journey of one of the figures, Asafri Jaya Bakri, starting from an academic to a politician. This research uses 4 stages, namely, first, heuristics, namely the stage of collecting sources in the form of archives, documents, etc. Second, source criticism is testing the data by conducting internal and external criticism of the authenticity of the data obtained. The third is interpretation, which is the interpretation of data so that it becomes a meaningful fact. The final stage is writing history in the form of a thesis. The result of the research is that Asafri Jaya Bakri began his career as an academic in 1984, he had held several strategic positions until his peak when he received a professorship at IAIN STS Jambi in the field of Islamic law/fiqh siyasah in 2000. But in 2011, when he served as Chairman of STAIN Kerinci, AJB switched his profession as a politician by becoming Mayor of Sungai Penuh for two terms from 2011-2016 and 2016-2020. Asafri Jaya Bakri's career has been spent holding positions both as an academic and politician. AJB has also been rumored to have committed KKN, one of which is nepotism, where some of his family and children get positions in the government.